Pengenalan dan Implementasi Metode Teams-Games-Tournament sebagai Inovasi Pembelajaran Kreativitas Anak di TK Negeri Pembina Kecamatan Janapria - Nopiani, Ema; Gunawan, Gunawan; Nurhasanah, Nurhasanah (Indonesian Publication Center, 2023)
This community service activity aims to introduce and implement the Teams-Games-Tournament (TGT) method as an innovative learning approach to enhance the creativity of children aged 5-6 years at TK Negeri Pembina, Janapria District. Initial observations revealed that teachers often face challenges in applying learning methods that stimulate children's enthusiasm and creativity, leading to limited imagination and social interaction among children. The TGT method, which involves competitive group learning, is believed to create an enjoyable and collaborative learning environment. In this activity, teachers received training and guidance on TGT steps, such as team formation, theme explanation, and the implementation of interactive games, particularly in cake decorating activities. The results of this service indicate an increase in teachers' understanding and skills in applying the TGT method, as well as greater enthusiasm from children in actively participating in learning activities. It is hoped that the continuous implementation of TGT can support the development of creativity and social interaction in early childhood.